Core decompression combined with intralesional autologous bone marrow derived cell therapies for osteonecrosis of the femoral head in adults: A systematic review and meta-analysis. Issue 3 (June 2023) - Saini, Uttam; Jindal, Karan; Rana, Anurag; Aggarwal, Sameer; Kumar, Prasoon; Sharma, Siddhartha
Abstract: Background: Core decompression (CD) is beneficial in the early stage of osteonecrosis of the femoral head (ONFH). Adjunctive bone marrow derived cell therapies (BMDCT) have been advocated which potentially aid the regenerative process. Question/purpose: This study was conducted to determine potential benefit of CD + BMDCT in ONFH, in terms of disease progression, conversion to arthroplasty (primary outcomes), and functional outcomes and complication rates (secondary outcomes). Methods: A systematic review of literature was performed on 3 databases. Studies reporting CD + BMDCT (intralesional instillation) in ONFH, with a minimum follow up of 1 year and reporting the pre-defined outcome measures were included in the review. Meta-analysis consisted of two different arms: a comparative arm, to compare CD + BMDCT to CD alone, and a non-comparative meta-analysis arm, to determine pooled rates of disease progression, conversion to arthroplasty and complication rates. Results: A total of 18 studies were included in the systematic review. CD + BMDCT had lower rates of disease progression (OR 0.19 [95% CI, 0.09, 0.40]) and conversion to arthroplasty (OR 0.20 [95% CI, 0.11, 0.40]) as compared to CD alone. Functional score (MD = −7.07 [95% CI, −12.28, −1.86]) and visual analog scale also showed better improvement with the use of CD + BMAC (MD = −10.39 [95% CI, −12.87, −7.90]). Increasing age and post-collapse stage at presentation were noted to have an adverse effect on the outcomes. Conclusion: CD + BMDCT was found to decrease disease progression and conversion to arthroplasty, and was noted to have better functional outcome scores as compared to CD alone. Highlights: This was a systematic review and meta-analysis. We evaluated core decompression (CD) + bone marrow derived cell therapies (BMDCT) CD + BMDCT was found to decrease disease progression and conversion to arthroplasty. HHS and VAS also showed better improvement with the use of CD + BMDCT Stage 3 avascular necrosis & younger age were associated with disease progression.